Is there a diurnal difference in mortality of severely injured trauma patients?. Issue 4 (6th December 2013) - Dybdal, Bitten; Svane, Christian; Hesselfeldt, Rasmus; Steinmetz, Jacob; Sørensen, Anne Marie; Rasmussen, Lars S
Abstract : Background: Mortality may be higher for admissions at odd hours than during daytime, although for trauma patients results are conflicting. The objective of this study was to assess whether diurnal differences in mortality among severely injured trauma patients in Denmark were present. Methods: This observational cohort study was conducted between 1 December 2009 and 30 April 2011 involving one level 1 trauma centre and seven local emergency departments in eastern Denmark. Patients were consecutively included if received by a designated trauma team. Night-time patients (20:00–07:59) were compared with daytime patients (20:00–07:59). An injury severity score (ISS) >15 defined severe injury. Patients with burns and patients who upon arrival were declared non-trauma patients were not included. The primary outcome measure was 30-day mortality. Results: A total of 1985 patients were recorded, of whom 576 were admitted at night-time, 1369 at daytime and 40 not included due to missing data. There were 142 patients with ISS >15 in the daytime group and 64 at night-time. The 30-day mortality was 14.1% for admittance at night-time versus 21.3% at daytime (p=0.22). Logistic regression analysis revealed that odd-hour admission was not a significant predictor of mortality for patients with ISS >15 when adjusted for age, ISS and initial treatment facility (OR 0.71 (95% CI 0.27 to 1.90); p=0.50). Conclusions: In conclusion, we found no diurnal differences in 30-day mortality for severely injured trauma patients.